2015
DOI: 10.1037/ort0000075
|View full text |Cite
|
Sign up to set email alerts
|

Suicide risk assessments: Examining influences on clinicians’ professional judgment.

Abstract: Professional judgment in complex clinical situations such as the assessment of suicide risk encompasses a multifaceted cognitive understanding of the substantive issues, technical expertise, and emotional awareness. This experimental design study investigated the degree to which the previous work-related experiences of clinicians and their preexisting emotional state influence professional judgment regarding acute risk in patients presenting with suicidal ideation. Experienced social workers and social work st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…Although providers who had had patients die by suicide did not differ in safety plan decision-making, providers who indicated one or more personal exposures to suicide (e.g., losing a friend to suicide, personally experiencing suicidal thoughts or attempts) were more likely to complete safety plans with patients. This result corresponds to studies that indicate that clinical decision-making regarding the treatment of those struggling with suicide-related concerns can be impacted by a myriad of personal factors of the provider [17,18]. Variation in when safety planning is implemented may indicate a need for clearer recommendations regarding which clinical presentations should prompt safety planning and for greater discussion of how attitudes towards suicide may impact patient care.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Although providers who had had patients die by suicide did not differ in safety plan decision-making, providers who indicated one or more personal exposures to suicide (e.g., losing a friend to suicide, personally experiencing suicidal thoughts or attempts) were more likely to complete safety plans with patients. This result corresponds to studies that indicate that clinical decision-making regarding the treatment of those struggling with suicide-related concerns can be impacted by a myriad of personal factors of the provider [17,18]. Variation in when safety planning is implemented may indicate a need for clearer recommendations regarding which clinical presentations should prompt safety planning and for greater discussion of how attitudes towards suicide may impact patient care.…”
Section: Discussionsupporting
confidence: 73%
“…Thus, self-administration of safety plans may result in a lower rate of safety plan completion or retention. Finally, prior research indicates that clinical decision-making regarding the treatment of suicide-related behaviors can be impacted by a myriad of personal factors of the provider [17,18]. For example, research has demonstrated that the more religious a clinician reports being, the more likely they are to believe a patient requires hospitalization due to suicide risk [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on workplace related PTSD has primarily examined mental health counsellors, nurses, and emergency responders [19]. In these studies the incidence of symptoms indicating a PTSD diagnosis ranged from social workers at 22.5% [20] to mental health nurses at 14%, and 17% [21] and ranged across all groups from 7% to 44% [22]. Differing methodologies may account for a substantial portion of this range of prevalence and most often, these studies connected traumatic stress symptoms with identifiable, specific, major work-related incidents rather than a wider range of traumatic experiences which most staff in the homeless sector 5 encounter.…”
mentioning
confidence: 99%
“…However, clinicians have difficulty considering multiple risk factors at once and appropriately adjusting risk determinations. Furthermore, clinical decision making suffers from significant individual variability, and decision making is influenced by several personal factors, such as provider age, case load, provider marital status, and religiosity (Berman, Stark, Cooperman, Wilhelm, & Cohen, ; Regehr, LeBlanc, Bogo, Paterson, & Birze, ). The use of predictive models may circumvent these concerns and they are less sensitive to individual variability.…”
mentioning
confidence: 99%